2020
DOI: 10.3390/antiox9121303
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide and Carnosine: Modulation of Oxidative Stress and Inflammation in Kidney and Brain Axis

Abstract: Emerging evidence indicates that the dysregulation of cellular redox homeostasis and chronic inflammatory processes are implicated in the pathogenesis of kidney and brain disorders. In this light, endogenous dipeptide carnosine (β-alanyl-L-histidine) and hydrogen sulfide (H2S) exert cytoprotective actions through the modulation of redox-dependent resilience pathways during oxidative stress and inflammation. Several recent studies have elucidated a functional crosstalk occurring between kidney and the brain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 316 publications
(387 reference statements)
0
19
0
Order By: Relevance
“…As previously stated, catechin, a type of flavonoid, suppressed the elevation of postprandial glucose more effectively when taken in the evening than in the morning, suggesting that the metabolic response of polyphenols may depend on their intake timing (21). Dietary polyphenols' health promoting effects are reported to be in a hormetic doseresponse manner, partly via the upregulation of Nrf2 pathway (44)(45)(46)(47). Therefore, in addition to the analysis of nutrients that we have conducted, analysis of the intake timing and volume of dietary polyphenols may provide a clearer view.…”
Section: Discussionmentioning
confidence: 92%
“…As previously stated, catechin, a type of flavonoid, suppressed the elevation of postprandial glucose more effectively when taken in the evening than in the morning, suggesting that the metabolic response of polyphenols may depend on their intake timing (21). Dietary polyphenols' health promoting effects are reported to be in a hormetic doseresponse manner, partly via the upregulation of Nrf2 pathway (44)(45)(46)(47). Therefore, in addition to the analysis of nutrients that we have conducted, analysis of the intake timing and volume of dietary polyphenols may provide a clearer view.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown the function of physiological and pathophysiological roles of H 2 S in the brain including traumatic brain injury 14 , 15 . Furthermore, other studies have pointed out the close interrelationship between H 2 S, neuroinflammation and Nrf2 16 , 17 .…”
Section: Introductionmentioning
confidence: 93%
“…The crosstalk, mediated by reactive oxygen species and inflammatory markers, may contribute to the high prevalence of cognitive impairment observed during the progression of CKD. Emerging data suggests that the metabolic interactions of the "kidney-brain axis" are likely mediated-at least in part-by the activities of hormetic processes and a phenomenon dependent on the severity of disease (63,64). Oxidant-induced inflammatory pathways could be promising therapeutic targets for the protection of neurocognitive function in developing children who have CKD.…”
Section: Disease or Development: Delineating Risk Factors For Brain A...mentioning
confidence: 99%